Flipped Classroom for enhancing fluency in secondary students from a public school: Aula invertida para mejorar la fluidez en estudiantes de secundaria de una escuela pública - Solórzano Alcívar, Emili (Revista Ecos de la Academia, 2022)
Abstract Modern pedagogy proposes constant changes in educational purposes and approaches based on the specific needs of students and individual learning styles. This condition separates traditional educational models from new innovative and creative models strengthened by the use of digital technologies and tools. The present investigation carries out a qualitative and quantitative analysis of the Flipped Classroom model, the benefits and procedures for its application from teaching as teaching strategies and from the student's point of view as a motivating model where he actively participates in the construction of knowledge and improvement of the academic performance as a result of its proper application.
Keywords: Keywords: Educational approaches; innovative models; knowledge construction.